2006
DOI: 10.1158/1535-7163.mct-05-0377
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small topoisomerase I–binding peptide that has synergistic antitumor activity with 9-aminocamptothecin

Abstract: The topoisomerase I (top1) -targeted camptothecin class of anticancer drugs is important in the treatment of several types of cancers. This class of drug inhibits the top1 enzyme during its catalytic DNA relaxation cycle, stabilizing the transient covalent top1-DNA complex by simultaneous noncovalent interactions with DNA and top1. We examined top1 using phage display because of the significance of this known top1-directed drug action. Several peptides that bind top1 were discovered and these were examined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Phage display peptide libraries have been previously used to identify inhibitors of enzyme activity (da Silva et al ., 2002; Pond et al ., 2006). We used a phage display kit from New England BioLabs to perform this screen together with the C‐terminal portion of EhMLBP (from amino acids 141 top 296), which includes the DNA‐binding domain of this protein (Lavi et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Phage display peptide libraries have been previously used to identify inhibitors of enzyme activity (da Silva et al ., 2002; Pond et al ., 2006). We used a phage display kit from New England BioLabs to perform this screen together with the C‐terminal portion of EhMLBP (from amino acids 141 top 296), which includes the DNA‐binding domain of this protein (Lavi et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…A literature search showed that 4 out of the 34 selected peptides (PFA (47), GLD (48), SAY (49), and HAA (50)) had been selected before by other groups for very diverse purposes. Two possible explanations could account for this observation.…”
Section: Discussionmentioning
confidence: 99%
“…A search of present literature published between 2005 and 2006 revealed > 30 papers that disclose the identification of peptides using phage display, which were demonstrated to specifically target proteins in vitro. The technology has been used in attempts to develop novel targeting therapeutics or diagnostic reagents for human cancers [23,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], HIV infection [59,60], human papilloma virus infection [61], obesity [62], bacterial infection [63][64][65][66], parasitic infection [67], autoimmune disorders [68], thrombosis and inflammation [69,70], Alzheimer's disease [71] and increasing vaccine efficacy [72]. However, the in vivo therapeutic efficacy of these novel peptides remains to be determined.…”
Section: Potential Target-specific Peptides Identified Using Phage-dimentioning
confidence: 99%